Research on the relationship between work-family conflict and burnout among civil aviation pilots after the COVID-19 pandemic - Weiheng Chen; Shouxi Zhu; Kequan Shao; Kejia Liang (PLoS ONE, 2026)
To examine the impact of work-family conflict on occupational burnout among pilots following the COVID-19 pandemic, this study employed the Maslach Burnout Inventory-General Survey and the Zhao Xinyuan Bi-directional Scale of Work-Family Conflict as research instruments. The data were analyzed using correlation analysis and Structural Equation Modeling (SEM) to explore the relationship between work-family conflict and burnout. The results indicate a significant correlation between work-family conflict and burnout, as well as the three dimensions of burnout. Specifically, the correlation coefficients between work interfering with family (WIF) and family interfering with work (FIW) with occupational burnout were found to be 0.737 and 0.496, respectively. In the path analysis of the SEM, the estimated effects of WIF and FIW on burnout were both 0.49. Mediation analysis revealed that WIF indirectly influences burnout through FIW, with a mediation effect value of 0.117. Additionally, while pilot-related factors did not significantly affect burnout, they were found to have a notable impact on work-family conflict. These findings underscore the significant role of work-family conflict in contributing to burnout and provide a theoretical foundation for targeted interventions aimed at mitigating burnout among pilots.